Β-Glucan successfully stimulated the immune system in different jawed vertebrate species. (February 2019) - de Oliveira, Carlos A.F.; Vetvicka, Vaclav; Zanuzzo, Fábio S.
Highlights: Diets with two β-glucan molecules were examined in four vertebrate species. β-Glucans exhibited different magnitudes of effects on immune responses. β-Glucans promoted immune stimulation in immune responses in all species. Abstract: Several reports have shown the positive effects of β-glucans on the immune. Howeverthese studies have a broad experimental design including β-glucans compounds. Consequently, a study using the same β-glucan molecule, administration route and experimental design is needed to compare the effects of β-glucan across vertebrate species. For this end, during 28 days we fed four different vertebrate species: mice, dogs, piglets and chicks, with two β-glucan molecules (BG01 and BG02). We measured the serum interleukin 2 as an indicator of innate immune response, the neutrophils and monocytes phagocytosis index as a cellular response and antibody formation as an adaptive response. The results clearly showed that the different β-glucan molecules exhibited biologically differently behaviors, but both molecules stimulate the immune system in a similar pattern in these four species. This finding suggests that vertebrates shared similar mechanisms/patterns in recognizing the β-glucans and confirms the benefits of β-glucans across different vertebrate species.